Diet Quality of Congregate and Home-delivered Meal Recipients in the United States (P04-076-19) - Ashour, Fayrouz Sakr (Curr Dev Nutr, 2019)
OBJECTIVES: 1) Examine diet quality of OAANSP meals, 2) examine diet quality of complementary food consumed in addition to the CM/HDM meal, and 3) examine diet quality of daily intake by individuals who did versus did not consume a CM/HDM meal. Background: Older adults are becoming a larger proportion of the US population, a phenomenon that will continue over the next few decades. Congregate (CM) and home-delivered meals (HDM) of the Older Americans Act Nutrition Program (OAANP) have beneficial effects on the lives of older adults. Yet, data demonstrating value remains relatively limited, arguably leading to underfunding. METHODS: Data from the Administration for Community Living (ACL) Outcomes Evaluation Study was collected using a multistage clustered sample design. Data collection tools comprised a survey (including information on respondent's sociodemographics, health status, self-reported weight and height, social relationships, dietary self-reliance, participation in other nutrition assistance programs, and food security) and two 24-hour recalls. HEI-2010 was used to calculate individual and mean scores using the simple HEI scoring algorithm and the population ratio method, respectively. Radar plots were used to visualize HEI comparisons, and multiple logistic regression models were built to examine associations between diet quality and OAANSP. RESULTS: OAANSP participation was associated with HEI (P < 0.0001 and P = 0.04 for CM and HDM, respectively) and so was number of meals/day (P = 0.007 and P = 0.03 for CM and HDM, respectively). Compared to the complementary diet, OAANSP meals had better scores for total vegetables (P < 0.0001), and greens and beans (P < 0.001). The complementing diet quality for CM participants had better scores than the meal for total fruit, whole grains, seafood and plant proteins; and whole grains for HDM participant. Meals and complementing foods exceeded the dietary guidelines for sodium, refined grains, saturated fat, added sugar and total protein. HDM participants’ mean HEI score was lower on no meal-day compared to meal-day (P < 0.0001). CONCLUSIONS: CM/HDM meals may need to be revised, especially for sodium, added sugar and refined grains. Adding another meal daily and expanding nutrition education may be important for a healthier diet. FUNDING SOURCES: None.